The media coverage of the suicide death of Verónica Forqué - Eizmendi Iraola, Maider; Gurrutxaga Rekondo, Guillermo (Revista Española de Comunicación en Salud, 2024)
Introduction: The suicide of Spanish actress Verónica Forqué generated ethical debate on the media treatment of such cases, highlighting the risk of the Werther effect (contagion) versus the potential Papageno effect (prevention). The WHO encourages a cautious approach to the issue. Objectives: To determine the characteristics and adherence to WHO recommendations of the coverage of the death by suicide of the actress Verónica Forqué in the Spanish media. Methodology: Content analysis is used, as well as inductive and deductive analysis of the news published by Elpais.com, Elmundo.es and ABC.es between December 13, the date of the actress’ death, and December 31 2021. Results: The Spanish general media offered extensive coverage of the death by suicide of Verónica Forqué. They did so, above all, in the Culture section, with information based, especially, on friends and relatives, and with limited adherence to the WHO recommendations. Discussion: The current codes of ethics are committed to limited coverage of the suicide of relevant people and to having expert sources and information on resources to prevent it. Conclusions: the coverage of Verónica Forqué’s death by suicide was based on her celebrity status and was broader than that of anonymous people. The media partially adheres to the WHO recommendations. The study puts on the table the need to work on specific guidelines or criteria to address death by suicide of celebrities.